Rwa: Novel Heuristic Algorithm for Optical Networks with Dynamic Traffic - Rodriguez-Garcia, A (Springer Verlag, 2016)
This article proposes the snake-one heuristic for the solution of the problem of routing and wavelength assignment in WDM optical networks with dynamic traffic. This heuristic is simulated in the NSFNET network with 3 other heuristics such as simulated annealing, genetic algorithms and tabu search. The results show that this new heuristic improves the blocking probability indicator, until 140 Erlangs. However, the network utilization indicator aggravated by any load. This heuristic allows the emergence of a new generation of algorithms where the objective is focused on improving network utilization indicator. The research team is already working in two variations of this heuristic, called snake-two and snake-three. It is expected that both algorithms, improve indicators of way simultaneously. © Springer International Publishing Switzerland 2016.
Keywords: Genetic algorithm; Simulated annealing; Tabu search; Wavelength